Early research results on the strength assessment of cylindrical shells with dents using an ai-based approach - Onatskyi, Roman (National Technical University "Kharkiv Polytechnic Institute", 2025)
Cylindrical pressure vessels often suffer from dents during long term operation. Traditional strength analysis methods can be slow or may yield overly conservative results. This study investigates the application of the use of artificial intelligence, to rapid assessment structural integrity. As an initial phase focused on methodology development, the early results based on a dataset generated by finite element simulations of rectangular plates were presented.
Keywords: clindrical shells; dents; structural integrity; finite element method; FE; artificial intelligence; AI; machine learning; ML; PINNs